Radicalism and Deradicalization at Institutions of Islamic Education - Sipuan, Sipuan (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2024)
Research discusses the phenomenon of radicalism and redicalization among students, so the young generation in Indonesia will be more critical, intelligent, enlightening, and have a high commitment to the future of this nation and country. The research method used is library research, namely data collection techniques by conducting study studies of books. The analysis of this research uses descriptive-qualitative, namely research that does not use statistical tests in data processing. There are two kinds of data sources used in this study, namely primary sources and secondary sources, which are related to radical Islam and moderate Islam. The results showed that radicalism in educational institutions was very influential on anarchic actions because of fanaticism. In educational institutions tainted with radical thoughts, it is usually seen from the way the education system is eccentric as if it is rational and usually does not hesitate to act anarchist. This is because they always think of themselves as the most correct, and it is not taught that students or educators will commit violence which is certainly strictly prohibited in Islamic education. In order to create deradicalization in Islamic educational institutions, the educational curriculum must contain subject matter that is normative-doctrinal-deductive and historical-empirical-inductive in nature, as a balance between material in the form of text and context. Thus, the curriculum content given in education is normative in nature and concrete cases in society so that children can understand and be aware of real situations that are full of differences.